A Novel UWB Antenna with Two Ultra Narrow and Closely Space Notched Bands. Issue 6 (March 2019) - Gong, Bing; Ma, Chuang; Jing, Fan; Hou, Yaling; Shen, Ruibing
Abstract: A novel compacting print planar monopole UWB antenna with two ultra narrow and closely space band-notched characteristics for low WLAN (5.15∼5.35GHz) and high WLAN (5.725∼5.825GHz) applications is presented. The antenna is one of the smallest UWB antenna found in the open literatures because of its overall size of 20×16 ×0.8(mm 3 ). Especially, by employing two open-circuited stub pairs (OCSPs), dual-band-notched characteristics are achieved. The notched bands is ultra narrow of 0.26GHz and 0.18GHz, respectively, to suppress the interferences of lower and higher WLAN band just enough. And the space between two notched bands is 0.53GHz. These features make a good proof that OCSP could reject narrow bands in both antenna and BPF.